PEMAHAMAN DASAR AKUNTANSI BAGI SISWA-SISWI SMA KATOLIK SANTO KRITROFORUS 1 - JAKARTA - Hendro Lukman; Joan Yohanes; Phebe Callista (PROSIDING SERINA, 2021)
Accounting science is a social science that is not fully related to social activities. Accounting is a social science that requires the math ability to study and understand it. The logic used in this science is similar to the exact sciences, because it requires a standard. Like other exact sciences, studying accounting requires routine, integrated exercises. Not all high schools can facilitate routine and integrated accounting practice activities. The same was experienced by Catholic High School St. Kristoforus  1 Jakarta. To improve the knowledge and skills of these high school students in the field of accounting, the "Pengabdian Kepada Masyarakat" team of the S1 Accounting study program at Universitas Tarumanagara, which has experience in running an accounting laboratory, formed an Accounting Laboratory class at the school. Classes those provide discussion of integrated accounting cases from capturing transactions to preparing financial statements for service companies and trading companies. The school makes this activity an optional extracurricular for class XII. This activity is the first meeting of the entire series of laboratory classes that discusses the introduction and basic concepts of accounting which consists of understanding accounting, accounting processes, accounting for service and trading companies, and desain of chart of accounts. The method used is to provide theory briefly, discuss questions and then discuss cases that are integrated with subsequent meetings. The results of this training were considered quite successful as measured by the quiz answers given at the end of the meeting, and supported by the results of the evaluation using the google form. The implication of this activity is that students have skills in the field of accounting, the school that organizes it gets added value, and for Universitas Tarumangara  as a marketing tool, not just as a community service activity.